PENGARUH PENDIDIKAN KONSUMEN TERHADAP PERILAKU KONSUMSI MAHASISWA - Nadila Aulia Rahmi; Vina Gabriella Saragih (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to analyze the influence of consumer education on student consumption behavior in higher education institutions. The phenomenon of increasing consumerism among students serves as the background for the importance of consumer education as an effort to shape rational and responsible consumption behavior. This study employs a quantitative approach with a survey method involving 250 students from various faculties. Data analysis uses multiple linear regression to measure the influence of consumer education variables including product knowledge, price awareness, evaluation capability, and financial literacy on consumption behavior. The results indicate that consumer education has a significant positive effect on student consumption behavior with a coefficient of determination (R²) of 0.687 (68.7%). Financial literacy variable has the most dominant influence (β=0.412, p<0.001), followed by price awareness (β=0.298, p<0.001), evaluation capability (β=0.267, p<0.01), and product knowledge (β=0.189, p<0.05). This research concludes that comprehensive consumer education can shape more rational, efficient, and sustainable consumption behavior among students.